Solar battery plate - XU JIE; ZHOU PING; ZHU MINJIE; XIA ZHENGYUE; XING GUOQIANG; YAN XINCHUN (2018)
The utility model provides a solar battery plate, it includes the silicon chip and sets up the electrode on the silicon chip. Electrode package draws together and sets up in the first main grid line of the first face of silicon chip, with a plurality of first thin grid line of first main grid line connection and set up in the dihedral a plurality of second main grid line of silicon chip. The arrayorientation of first main grid line is unanimous with the array orientation of second main grid line, and just the two quantity is the same. Same apart from the homogeneous phase with between the adjacent second main grid line between every adjacent first main grid line, and array orientation is last, the setting of staggering each other of first main grid line and second main grid line to make each first main grid line and the second main grid line corresponding and constitute a pair of electrode unit, first main grid line and second main grid line at least one adopts the discontinuous design. The sliced grid line d